Investor's Preference and Awareness in Financial Instruments in Nepal - Basnet, Krishna (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
The research aimed to examine the Nepalese investors' awareness and preference for investment in different sectors of investment An analytical approach has been followed to analyze the related data and relationship among variables. This study mainly based on primary data. Information was collected through questionnaire. Mail questionnaire method of collection data are employed to collect primary data. Only 60 filled up questionnaires has been systematically analyzed.It is imperative to conclude that investors seem to be less concern over social status and to be concern over sufficient return and less risk so far as the matter of investing in securities is concerned. Earnings per share (EPS), rate of return, dividend per share (DPS) and management of company are the consideration factor those can be regarded as the most important factor determining their choice of security. Dividend, capital gain, bonus share and liquidity are the major motivating factors for investors to invest in securities, whereas right share and voting rights is only important factors. The debt and preferred stock in Nepalese securities market have no provision of handsome return that compensates the perceived risk of investors. So, investors are less inclined toward these securities. The reason that these securities are illiquid and less marketable, investors tends to have negative attitude towards these securities. Most of the investors set the investment policy while investing in securities.